The abnormal vitreomacular adhesion corresponding serous macula detachment area as a possible ocular risk factor in central serous chorioretinopathy - Turgut, Burak; Gungor Kobat, Sabiha; Catak, Onur (Gazi Eye Foundation, 2020)
Purpose: To investigate the frequency of abnormal vitreomacular adhesion (VMA) in central serous chorioretinopathy (CSCR) using spectral domain optical coherence tomography (SD-OCT). Materials and Methods: In this observational retrospective case-study, the OCT scans of 30 patients with acute CSCR (Group 1) and 15 patients with chronic CSCR (Group 2) cases which were diagnosed based on clinical, ophthalmological and OCT findings and which was followed in our hospital and 30 control subjects without retinopathy (Group 3) were retrospectively reviewed. The frequencies of VMA in the groups were evaluated. Results: 31 eyes of 30 patients had acute CSCR and 20 eyes of 15 patients had chronic CSCR. The control group included 30 normal eyes of 30 healthy control subjects. It was found that the frequency of VMA was 38,7% (12 eyes), 50% (10 eyes), 20% (6 eyes) in Group 1, Group 2 and Group 3, respectively. The difference among the frequency of VMAs in groups was statistically significant (p<0.05, p<0.05, p<0.05, respectively). Conclusion: This pilot study suggests that there is difference between the frequencies of VMA in the patients with CSCR and control group. © 2020 Gazi Eye Foundation. All rights reserved.
Keywords: Central serous chorioretinopathy; Optical coherence tomography; Vitreomacular adhesion